A Computational Study of Artery Curvature and Endograft Oversize Influence on Seal Zone Behavior in Endovascular Aortic Repair - Cerda-Villablanca, E (Elsevier Ltd, 2024)
Thoracic endovascular aortic repair (TEVAR) is a minimally invasive procedure involving the placement of an endograft inside the dissection or an aneurysm to direct blood flow and prevent rupture. A significant challenge in endovascular surgery is the geometrical mismatch between the endograft and the artery, which can lead to endoleak formation, a condition where blood leaks between the endograft and the vessel wall. This study uses computational modeling to investigate the effects of artery curvature and endograft oversizing, the selection of an endograft with a larger diameter than the artery, on endoleak creation. Finite element analysis is employed to simulate the deployment of endografts in arteries with varying curvature and diameter. Numerical simulations are conducted to assess the seal zone and to quantify the potential endoleak volume as a function of curvature and oversizing. A theoretical framework is developed to explain the mechanisms of endoleak formation along with proof-of-concept experiments. Two main mechanisms of endoleak creation are identified: local buckling due to diameter mismatch and global buckling due to centerline curvature mismatch. Local buckling, characterized by excess graft material buckling and wrinkle formation, increases with higher levels of oversizing, leading to a larger potential endoleak volume. Global buckling, where the endograft bends or deforms to conform to the centerline curvature of the artery, is observed to require a certain degree of oversizing to bridge the curvature mismatch. This study highlights the importance of considering both curvature and diameter mismatch in the design and clinical use of endografts. Understanding the mechanisms of endoleak formation can provide valuable insights for optimizing endograft design and surgical planning, leading to improved clinical outcomes in endovascular aortic procedures. © 2024 Elsevier Ltd